Studies on Azo dye degradation using green synthesized nanoparticles - Shivani, Palugula S.; kumari, S. Chaitanya; Padma, P. Naga (International Journal of Scientific Research in Biological Sciences, 2019)
Release of textile Azodyes from industries is a health issue of concern as they are carcinogenic. Azodyes mostly act as recalcitrant molecules which are polluting the environment and so biodegradation of azodyes is necessity. Green synthesized nanoparticles can be used to biodegrade different azodyes. The present study is concentrated on biodegradation of azodyes using nanoparticles synthesized from seven different plant extracts like Camellia sinensis, Mentha officinalis, Ocimum tenuiflorum, Piper betle, Punica granatum, Aloevera and Amaranthus. Copper Nanoparticles (CuNPs) and Silver Nanoparticles (AgNPs) were synthesized using different aqueous solutions like CuSO4 and AgNO3 respectively. Synthesis of nanoparticles was studied at various time intervals like 24hrs, 48hrs and 72hrs. The Azodyes were studied for decolorization at varying time intervals. Various azodyes studied includes congo red, tryphan blue, methyl red and malachite green at different concentrations ranging from 0.2 mg/mL - 1.0 mg/mL. AgNP’s produced by Aloevera and Ocimum tenuiflorum has shown degradation of only two different azo dyes methyl red and malachite green respectively. The same results obtained by CuNPs synthesized from leaf extracts of Mentha officinalis, Camellia sinensis, Piper betle and Punia granatum which showed degradation of same azo dyes methyl red and malachite green. Whereas AgNPs produced by Amaranthus has shown the degradation of three different azo dyes congo red, malachite green and methyl red. However, tryphan blue could not be degraded by any of the nanoparticles. Comparatively the degradation of azodye methyl red was found to be highest by AgNP’s synthesized from Camellia sinensis which varied with time and was 100% by 72 hours. The degradation of azodye malachite green was found to be highest by CuNP’s synthesized from Camellia sinensis which varied with time and was 100% by 72hours whereas the degradation of azo dye congo red was shown only by CuNP’s synthesized from Amaranthus which varied with time and was 91% by 72hours. Increased concentration of nanoparticles enhanced the azodye degradation resulting in decolourization within 48 hours. Thus, the green synthesized nanoparticles can be used for efficient degradation of different azo dyes giving scope for development of treatment technologies of industrial dye waste waters.